ABKK3203 political development and third world politics - Malik, Maszlee; Cheng Keat, Oo (OUM, 2016)
ABKK3203 Political Development and Third World Politics is one of the courses offered by Faculty of Applied Social Sciences at Open University Malaysia (OUM). By the end of this course, you should be able to: 1. Describe some of the major conceptual and theoretical issues in the field of political development; 2. Explain the changes in national and international politics and apply this knowledge to contemporary issues pertaining to Third World development issues generally; 3. Evaluate the cultural, economic, social, political and gendered dynamics of development; 4. Elaborate on theoretical and methodological discourse; and 5. Apply theoretical debates to concrete case studies from the Third World.